Pertanggungjawaban Tindakan Aborsi yang Dilakukan Pelaku : Perspektif Hukum Kesehatan - Surya Paramitha, Sagung Dinda; Purwani, Sagung Putri M. E (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024)DO - 10.24843/JMHU.2024.v13.i04.p11, 2025)
The purpose of writing this scientific article is as a material to deepen insight related to the perspective of criminal law and health law regarding the act of abortion and how the form of liability of the perpetrator who performs the act of abortion based on juridical perspective. Abortion is an act of miscarriage of the unwanted / unwanted pregnancy that is done intentionally and is an event that occurs as a result of a human action with his efforts so that a pregnancy can be aborted. When reviewing abortion in terms of the Criminal Code, there is no room for such actions. However, when looking at the Health Law (Law No. 36 of 2009 generally prohibits abortion, but there are special provisions that become exceptions so that abortion can be done. In this case there is a  misalignment between the two regulations.